2009
DOI: 10.1186/1471-2164-10-368
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation and fine-mapping of a major QTL for resistance to infectious pancreatic necrosis in Atlantic salmon (Salmo salar): population-level associations between markers and trait

Abstract: Background: Infectious pancreatic necrosis (IPN) is one of the most prevalent and economically devastating diseases in Atlantic salmon (Salmo salar) farming worldwide. The disease causes large mortalities at both the fry-and post-smolt stages. Family selection for increased IPN resistance is performed through the use of controlled challenge tests, where survival rates of sib-groups are recorded. However, since challenge-tested animals cannot be used as breeding candidates, withinfamily selection is not perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
276
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(283 citation statements)
references
References 43 publications
5
276
1
1
Order By: Relevance
“…same region of Atlantic salmon LG 21 explains much of the genetic variation in IPN resistance in fry (48%) and post-smolts (83%), and do not suggest a large role for any of the other LGs (Moen et al, 2009). The confirmation of the LG 21 major QTL by two independent research groups in two distinct populations is a strong evidence that the QTL effect is genuine and robust.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…same region of Atlantic salmon LG 21 explains much of the genetic variation in IPN resistance in fry (48%) and post-smolts (83%), and do not suggest a large role for any of the other LGs (Moen et al, 2009). The confirmation of the LG 21 major QTL by two independent research groups in two distinct populations is a strong evidence that the QTL effect is genuine and robust.…”
Section: Discussionsupporting
confidence: 49%
“…The largest QTL, on Atlantic salmon linkage group (LG) 21, was estimated to explain between 21 and 32% of the within-family phenotypic variation in IPN resistance during this field outbreak (Houston et al, 2008a, b), and was subsequently confirmed by Moen et al (2009). A further genome-wide significant QTL was detected on LG 28 (LG denoted as given in the ASalBase map http://www.asalbase.org/sal-bin/map/index), with a suggestive QTL on LG 19 (Houston et al, 2008b).…”
Section: Introductionmentioning
confidence: 98%
“…A quantitative trait loci explaining a very large proportion of the genetic variation in IPN resistance has been detected in Atlantic salmon (Houston et al, 2009;Moen et al, 2009). In our study, evidence was found of significantly favourable genetic correlations of resistance to furunculosis in unvaccinated fish with resistance to both IPN and ISA (unvaccinated fish).…”
Section: Discussionmentioning
confidence: 99%
“…A major QTL for IPN resistance in Atlantic salmon has been identified and confirmed Moen et al, 2009a). A four-marker haplotype has been identified that strongly segregates with IPN resistance in Norwegian Atlantic salmon broodstock, providing a solid framework for linkage-based MAS in this population (Moen et al, 2009a).…”
Section: Mas In Aquaculture 41 Examples Of Qtl-based Markers For Aqumentioning
confidence: 99%
“…It is no surprise therefore, that several QTL have been identified for body weight and condition factor in Atlantic salmon (Baranski et al, 2010;Boulding et al, 2008;Moghadam et al, 2007;Reid et al, 2005) (Moghadam et al, 2007;Kuttner et al, 2011). QTL for several other traits in salmonids have been mapped, including upper temperature tolerance (Jackson et al, 1998;Perry et al, 2001;Somorjai et al, 2003), spawning time (O'Malley et al, 2003), developmental rate (Nichols et al, 2008), and resistance to pathogens Gilbey et al, 2006;Houston et al , 2009Houston et al , 2010Jones et al, 2002;Moen et al 2007Moen et al , 2009a. Given that many of the microsatellite markers derived from one salmonid species amplify the DNA from other salmonid species, it has been relatively straightforward to carry out comparative analyses of the rainbow trout, Arctic charr and Atlantic salmon genomes .…”
Section: Quantitative Trait Loci (Qtl)mentioning
confidence: 99%